Phoneme Characteristic and the Perceptive Base - Balšaitytė, Danutė (Respectus Philologicus, 2002)
The acceptance of the language signal as a complex psychic process is conditioned by many factors among which a special role is assigned to the language system as well as its impact on the process of perception of the same language signals by the speakers of different languages. On the basis of the data gathered during class-room experiments, the article aims at the investigation of peculiarities of the Russian noise consonants by native Latvian speakers. Concrete perceptive characteristics of the Russian consonants, their differential features of perceptive base of native Latvian speakers have been distinguished. In the recognition of the consonant, its hardness / softness plays a significant role. The Russian soft consonants are identified by Latvian speakers with considerable difficulty in contrast to the corresponding hard consonants, which may be explained by considerable changes in the acoustic spectre of the soft consonants. The acoustic parameters of the soft consonants affect the recognition of the quality of the consonant, moreover, they bring difficulty in the perception of the differential features, especially regarding the method of their formation. The most established feature in the perceptive perspective is voice characteristics of the consonants. Native Latvian speakers’ ability to distinguish between the perception of Russian soft consonants allows of the possibility to speak about the existence of different degrees of palatalization (on the perceptive level) which depends both on the consonant’s belonging to a certain class and the quality of the neighbouring vowel.